Pencegahan dan Pengendalian Stunting Pada Balita Melalui Pemberian Makanan Tambahan Berbahan Dasar Produk Pangan Lokal - Tasya, Zhanaz; Yani, Ahmad; Lestari, Ayu; Amelia, Rezi (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Stunting or chronic malnutrition is a nutritional problem due to a lack of nutritional intake from food that lasts for a long time. Loru Village is one of the villages located in the Biromaru Health Center Working Area, Sigi Regency, Central Sulawesi Province, where Sigi Regency is the district with the highest stunting cases in Central Sulawesi Province and Biromaru Health Center is the Health Center with the highest stunting cases in Sigi Regency. In addition, Loru Village is one of the pumpkin producing areas in Central Sulawesi Province. So through this PKM activity, the partners or cadres of the integrated health post who will be empowered are 20 people, then this group will become a role model for the community. The goal for partners is to innovate Additional Food products in the form of pumpkin-based biscuits to prevent and control stunting and also improve community welfare, The results of this activity are an increase in knowledge and skills for partner groups, both in terms of increasing knowledge about stunting and its impacts, increasing knowledge about the benefits of pumpkin as additional food for toddlers, increasing skills in making biscuits from pumpkin and increasing skills about sustainable food gardens.